2003
DOI: 10.1002/ccd.10522
|View full text |Cite
|
Sign up to set email alerts
|

Sterile inflammation associated with transradial catheterization and hydrophilic sheaths

Abstract: In 1999, we noted the development of inflammation and/or abscesses at the site of radial access in a group of patients. Over a 3-year period, we noted this inflammation in 33 patients out of 2,038 (1.6%) who had catheterization via the radial approach. The radial abscesses occurred in 30 patients out of 1,063 (2.8%) in whom we could confirm the use of a hydrophilic-coated sheath, but in no patient for whom we can document that an uncoated sheath was used. No infectious agent could be implicated, and the time c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 12 publications
4
68
0
5
Order By: Relevance
“…Local foreign body reaction at the puncture site was described (2.8%-5.0%) in the cardiology literature after radial access by using long hydrophilic coated sheaths. [25][26][27] Two of our patients presented with aseptic secretion and local inflammation at the puncture site that did not respond to the initial antibiotic treatment, and eventually resolved spontaneously over a few months. Pathologic specimen was not obtained in these cases; however, the clinical picture corresponds to a foreign body skin reaction.…”
Section: Discussionmentioning
confidence: 93%
“…Local foreign body reaction at the puncture site was described (2.8%-5.0%) in the cardiology literature after radial access by using long hydrophilic coated sheaths. [25][26][27] Two of our patients presented with aseptic secretion and local inflammation at the puncture site that did not respond to the initial antibiotic treatment, and eventually resolved spontaneously over a few months. Pathologic specimen was not obtained in these cases; however, the clinical picture corresponds to a foreign body skin reaction.…”
Section: Discussionmentioning
confidence: 93%
“…Ceasing to use this hydrophilic-coated sheath has resulted in the disappearance of this complication. 9,13,22,23 There have been previous reports of catheter coating resulting in emboli in the cerebral and other vascular territories, 3,16 but few studies have reported on the biological effects of PVP and its derivatives on the cerebral vasculature. Polyvinylpyrrolidone is generally considered safe and has been approved by the FDA.…”
Section: Biological Effects Of Foreign Hydrophilic Emboli On the Vascmentioning
confidence: 99%
“…Further, the use of certain hydrophilic coatings (for example, those manufactured by Cook [12,13]) has been associated with the formation of sterile granulomas and abscesses [14][15][16][17][18]. Clearly, there is substantial room for improvement in the field of lubricious coatings for endovascular catheter use and, in particular, biodegradability would be a marked advantage.…”
Section: Introductionmentioning
confidence: 99%